Radiative properties of soot fractal superaggregates including backscattering and depolarization. (May 2020) - Ceolato, Romain; Paulien, Lucas; Maughan, Justin B.; Sorensen, Christopher M.; Berg, Matthew J.
Highlights: The superposition T-matrix method (STMM) is used to simulate light scattering from soot. The simulations cover a wide range of wavelength and several scattering observables. Comparisons between the STMM and Rayleigh-Debye-Gans approximation are made. The linear depolarization ratio is roughly 10 times larger for superaggregates than chain-like. Abstract: The modeling of radiative properties of soot particles can be addressed by a number of methods. Among them, the canonical Rayleigh-Debye-Gans (RDG) theory and the Superposition T-Matrix Method (STMM) are particularly well adapted to the task. Here, both RDG and STMM are used to model the radiative properties of two types of fractal aggregates indicative of soot relevant to lidar sensing. One type, a canonical aggregate with a chain-like morphology, corresponds to low-sooting flames and is well characterized by a single fractal dimension. The other type, a superaggregate, exhibits multiple fractal dimensions and is seen in heavily sooting flames. Radiative properties such as the differential scattering cross-section, total scattering cross-sections, backscattering cross-sections, and linear depolarization-ratio (LDR) are calculated for a range of wavelengths from 300 − 1100  nm while including the wavelength dependence of the soot refractive index. Of particular interest is that depolarization by a superaggregate is found to be approximately ten times larger than the depolarization by a canonical chain-like aggregate and both exhibit a power-law with wavelength. Results for specific wavelengths of interest to lidar (355, 532, and 1064 nm) are tabulated for lidar applications. Additionally, RDG theory yields fairly accurate results for modeling the radiative properties, including lidar relevant parameters such as backscattering cross-sections, only for canonical soot fractal aggregates.